The effect of chronic iron losses on liver regeneration in male and female rats - Zivna, Helena; Zivny, Pavel; Vokurkova, Doris; Svejkovska, Klara; Palicka, Vladimir (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2010)
BACKGROUND: We studied the effect of iron deficiency on liver regeneration and innate immunity - respiratory burst of PMN. METHODS: Wistar rats, males (M) and females (F) had sham withdrawals or males (M-w) and females (F-w) had nine blood withdrawals every week. All rats were sacrificed in 10(th) week after 67% hepatectomy (PH) after (3)H-thymidin application. We determined erythrocyte and leukocyte count, respiratory burst (RB), serum prohepcidin, estradiol, iron, iron binding capacity (TIBC) and liver iron stores. RESULTS: Liver DNA synthesis in M-w and F-w increased versus M and F (p=0.05). Serum prohepcidin after PH decreased in M, F (p=0.001) and F-w (p=0.05), but not in M-w. Blood withdrawals increased spontaneous RB (p<0.05), stimulated RB at females (p<0.01). Stimulated RB was lower in M-w then in M (p<0.01). Serum iron was lower in males than in females, but higher in rats with withdrawals than in rats without withdrawals. TIBC decreased after PH in M, F, F-w groups (p<0.001), less at M-w (p<0.05). Liver iron stores decreased in M, less in F. CONCLUSIONS: Both genders with blood withdrawals had early beginning of liver regeneration after PH. The preconditioning (withdrawals) leads to increase in iron turnover and stores following best reactivity of PMN, rapid decrease in serum prohepcidin, and early initiation of liver regeneration, mainly in females. We assume, the females have higher iron turnover, liver iron stores more easily mobilized for blood losses, because next gravidity physio logically begin immediately after birth. Simply transfer of experimental results to human medicine is difficult.
Keywords: Liver; regenerace jater; játra; Rats; Respiratory Burst; Male; kationické antimikrobiální peptidy; Hepcidins; Iron Deficiencies; deficit železa; respirační vzplanutí; Rats, Wistar; mužské pohlaví; Neutrophils; železo; Hemoglobins; krysa rodu Rattus; proteinové prekurzory; Protein Precursors; Liver Regeneration; Iron; ženské pohlaví; zvířata; Estradiol; neutrofily; Antimicrobial Cationic Peptides; hemoglobiny; potkani Wistar; Female; estradiol; hepcidiny; Animals